Unmasking domestic violence: Examining victim and perpetrator characteristics and injury patterns in Kuching, Sarawak - Chew, Keng Sheng; Shirly Wong, Siew Ling (Malaysian Medical Association, 2024)
Introduction: Domestic violence (DV) is a pervasive social and public health issue affecting millions globally, regardless of age, gender or socioeconomic background. Understanding victim and perpetrators' characteristics as well as the DV injury patterns are essential for developing targeted interventions and prevention strategies. Although past DV studies have often focused on female victims, it is increasingly recognised that DV affects a significant proportion of male victims as well. This study aimed to comprehensively examine both male and female DV victims and perpetrators, as well as the anatomical regions affected in DV cases in Kuching, Sarawak, so that a deeper understanding of DV within this community can be enhanced.